Analysis of the Implementation of Accounting Information Systems on Fund Management and the Improvement of Healthcare Service Quality at Putri Hijau Level II Hospital - Sayyida Nabila; Agus Tripriyono; Yunita Sari Rioni (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The implementation of an Accounting Information System through the Agency-Level Financial Application (SAKTI) plays a strategic role in enhancing efficiency, transparency, and accountability in public hospital fund management. This study aims to analyze the implementation of SAKTI and its impact on fund management effectiveness and healthcare service quality at Putri Hijau Level II Hospital. A descriptive qualitative method with a case study approach was employed. Data were collected through in-depth interviews, observation, and documentation from purposively selected informants, including financial staff, medical personnel, and patients. The results show that the implementation of SAKTI is effective, characterized by increased recording efficiency, accelerated data reconciliation, and increased transparency and accuracy of financial reports directly connected to the Ministry of Finance. The effectiveness of fund management has a positive impact on accelerated administration, smooth distribution of drugs and medical devices, and increased patient satisfaction. Despite technical constraints and resource limitations, the implementation of SAKTI has made a significant contribution to financial management and healthcare service quality at Putri Hijau Level II Hospital.